Prevalence and Risk Factors of Functional Dyspepsia: A Population-Based Study - Aydın, Selami; Oner, Can; Cetin, Hüseyin; Simsek, Engin Ersin (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: Functional dyspepsia is one of the most common functional gastrointestinal disorders and affects more than 20% of the population. This study aimed to determine the prevalence of functional dyspepsia according to Rome IV criteria and its relation with social determinants.Methods: This cross-sectional study was conducted in the Department of Family Medicine, Kartal Dr Lutfi Kırdar City Hospital Tuzla Training and Research Primary Health Care Center, Istanbul, Turkey from May - December 2019. The participants (aged 18-78) were selected using randomized sampling by a family physician according to the records. All participants underwent a clinical interview based on a questionnaire based on Rome IV criteria. The factors that were significant in the binary comparison were taken into logistic regression analysis (Backward: LR) to determine the causal relationship. P-values 0.05 were considered statistically significant.Results: A total of 350 participants were enrolled to the study (43.4 %; n=152 male and 56.6%; n=198 female). The prevalence of functional dyspepsia was 16.9% (n=59). 62.7% (n=37) of dyspeptic patients had epigastric pain syndrome and 67.8% (n=40) of them had postprandial distress syndrome. Daily tee consumption, body mass index, and family history were found as social factors related to functional dyspepsia.Conclusion: The prevalence of functional dyspepsia was 16.9% according to Rome IV criteria and most of the patients were female. Obesity was an important factor related to dyspepsia. Dyspeptic symptoms must investigate especially in obese female patients.